Review of catalytic reforming of biomass pyrolysis oil for hydrogen production - Zhang, Chengbing (Frontiers in Chemistry, 2022)
After more than 20 years of development, biomass rapid pyrolysis technology has become mature technically. However, its main product biomass pyrolysis oil (bio oil) has limited its application due to low energy density and poor thermal stability. Catalytic reforming is a feasible way for bio oil subsequent utilization to produce hydrogen its. In this paper, the research status and main research directions of bio oil catalytic reforming for hydrogen production are summarized, with emphasis on CO2 adsorption enhanced catalytic reforming for hydrogen production.